Cognitive impairment and dementia - V. A. Parfenov; S. V. Verbitskaya (Медицинский совет, 2018)
Cognitive impairment (CI) is one of the causes of acquired disability in post-stroke patients. The article presents an analysis of the prevalence, pathogenesis, manifestations, diagnosis, treatment and prevention of post-stroke CI. It is noted that CI can be caused not only by focal vascular brain damage, but also by the presence of concomitant vascular and degenerative lesions in stroke patients. The authors present the results of their own study of CI in 350 patients after stroke within 5 years. The treatment and prevention of CI progression are based on stroke prevention, non-pharmaceutical and pharmaceutical methods for improving cognitive functions. The article discusses data on the use of Cerebrolysin in post-stroke patients, the results of the two latter meta-analyses of Cerebrolysin use.